A load–indentation formulation for cement composite filled pipe-in-pipe structures. (1st June 2015) - Qian, Xudong; Wang, Yu; Richard Liew, J.Y.; Zhang, Min-Hong
Highlights: We investigate the load–indentation response of pipe-in-pipe composite structures. We propose a new load–indentation relationship for steel hollow pipes. We propose a two-stage model for load–indentation responses of composite pipes. Abstract: This study proposes a two-stage approach to predict the lateral load ( P ) versus the local indentation ( δ ) relationship for cement composite filled pipe-in-pipe structures. The first stage extends a theoretical shell model used in predicting the P – δ relationship for hollow steel pipes, to the sandwich composite pipes by introducing an equivalent thickness to describe the composite action. This composite action, however, deteriorates at large indentation levels. The indentation resistance in the second stage, therefore, combines the resistance of three individual layers of materials. This approach predicts closely the P – δ relationship measured for the pipe-in-pipe composite specimens under lateral loads.